2012
DOI: 10.1021/jp3061637
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Adsorption on Aluminosilicate Single-Walled Nanotubes of Imogolite Type

Abstract: Adsorption of CO 2 at subatmospheric pressure at temperatures about ambient has been studied on three materials: (i) imogolite (IMO, chemical formula (OH) 3 Al 2 O 3 SiOH)) a hydrated alumino-silicate occurring as nanotubes (NTs) with bridged AlOHAl groups at the outer surface and Si−OH groups at the inner surface; (ii) an imogolite-like material (Me-IMO, chemical formula (OH) 3 Al 2 O 3 SiCH 3 ) with Si-CH 3 groups replacing Si−OH at NTs inner surface; (iii) a material (Me-IMO-NH 2 ) obtained by grafting 3-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…The growing research in the photo-catalytic potential of 3D nano- and meso-porous silicates (Sastre et al, 2012a,b; Alarcos et al, 2017; Murcia-López et al, 2017), and parallel substantial progress in the synthesis and characterization of 1D-structured aluminosilicate (AlSi) nanotubes (NTs) based on the imogolite (Imo) structure (Wada et al, 1979; Barron et al, 1982; Theng et al, 1982; Mukherjee et al, 2005, 2007; Levard et al, 2008, 2010; Kang et al, 2010, 2011, 2014; Bottero et al, 2011; Yucelen et al, 2011, 2012b; Zanzottera et al, 2012a,b; Bonelli et al, 2013; Amara et al, 2015; Monet et al, 2018), have prompted recent exploratory computational studies of the potential of Imo-NTs for photo-catalytic applications (Teobaldi et al, 2009; Zhao et al, 2009; Poli et al, 2015, 2016; Elliott et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The growing research in the photo-catalytic potential of 3D nano- and meso-porous silicates (Sastre et al, 2012a,b; Alarcos et al, 2017; Murcia-López et al, 2017), and parallel substantial progress in the synthesis and characterization of 1D-structured aluminosilicate (AlSi) nanotubes (NTs) based on the imogolite (Imo) structure (Wada et al, 1979; Barron et al, 1982; Theng et al, 1982; Mukherjee et al, 2005, 2007; Levard et al, 2008, 2010; Kang et al, 2010, 2011, 2014; Bottero et al, 2011; Yucelen et al, 2011, 2012b; Zanzottera et al, 2012a,b; Bonelli et al, 2013; Amara et al, 2015; Monet et al, 2018), have prompted recent exploratory computational studies of the potential of Imo-NTs for photo-catalytic applications (Teobaldi et al, 2009; Zhao et al, 2009; Poli et al, 2015, 2016; Elliott et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…38 In both cases, an enhanced adsorption towards CO 2 and methane was evidenced, which could find applications in molecular separation, gas storage or catalysis. 35,37,38 While all these studies concern only silicon-based imogolite nanotubes, no data have been reported so far on germanium and Si/Ge modified nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the creation of double-walled (DW) AlGe NTs has also been achieved. [34][35][36][37] Important advances have been made in the post-synthetic, selective functionalisation of the outer or inner surface of AlSi NTs, [38][39][40] and in the direct creation of methylated (AlSiMe) 41,42 or aminated (AlSiAm) 43 AlSi NTs derivatives, with methyl (ZCH 3 , Fig. 1) or amine (ZNH 2 ) functions in the NT cavity, instead of silanol groups.…”
Section: Introductionmentioning
confidence: 99%
“…Further selective amination of the outer surface of AlSiMe NTs by post-synthesis grafting, yielding hybrid AmAlSiMe derivatives, has also been shown to be possible. 39,40 Exploration of the surface properties of these hybrid materials has revealed superior performances for chemical separation, [39][40][41][42][43][44] and results on their beneficial role as support for (photo)catalysts 45,46 as well as in hybrid nanocomposites 47 have started to appear in the literature.…”
Section: Introductionmentioning
confidence: 99%